MICROBIOLOGICAL INFECTION RISKS AMONG CHILDREN IN SUB-URBAN SETTLEMENT OF MAKASSAR - Hafsan, Hafsan; Anggraeni, Rini; Pratiwi, Afryanti (JURNAL SIPAKALEBBI, 2025)
Microbiological infections in children are still a significant health problem, especially in sub-urban environments with suboptimal sanitation infrastructure. Environmental factors and hygiene habits play a big role in increasing or decreasing the risk of infection. This study aims to analyze the relationship between home sanitation conditions, housing density, children’s hygiene habits, and the incidence of microbiological infections in children in Bontote’ne Housing, Makassar. This study uses an analytical descriptive study design with a cross-sectional approach. A total of 50 children aged 5–12 years and their parents participated as respondents. Data were collected through questionnaires regarding environmental factors, children’s hygiene habits, and history of microbiological infections. The analysis was performed using Chi-Square tests and logistic regression to identify the relationship between independent variables and bound variables. The results showed that poor sanitation, high residential density, and inadequate handwashing practices were significantly associated with increased rates of gastrointestinal, respiratory, and diarrhoeal infections. Handwashing with soap was identified as a key protective factor.This study confirms that environmental factors and hygiene habits have an important role in the incidence of microbiological infections in children. Public health interventions such as improving sanitation infrastructure, improving access to clean water, and ongoing hygiene education are needed to reduce the risk of infection in sub-urban environments.